Poverty and access to water and water governance institutions in Con Cuong district, Nghe An Province, Vietnam: Report on the results from a household questionnaire survey - Pham Thi Mai Huong; Le Thi Thanh Phuong; Thomas Skielboe; Helle Munk Ravnborg (Danish Institute for International Studies (DIIS), 2011)
In view of the increasing competition for water, there is a risk that particularly the rural poor will increasingly face difficulties in meeting their water needs for domestic and productive purposes. Based on a questionnaire survey carried out during 2008 in Con Cuong district, Nghe An province, Vietnam, this DIIS Working Paper provides a household poverty profile for the rural population of the district and analyses access to water enjoyed by the poor, less poor and non-poor households and their contact to water governance institutions.
Keywords: 300; Armut; Wasserversorgung; Wasserwirtschaft; Vietnam